Cover Image. Issue 4 (19th December 2021) - Pan, Neng; Zhang, Ruibin; Yang, Tiankai; Cui, Can; Xu, Chao; Gao, Fei
Abstract : The cover image is based on the Original Article Fast‐Tracker 2.0: Improving autonomy of aerial tracking with active vision and human location regression by Can Cui et al., https://doi.org/10.1049/csy2.12033 .